2018
DOI: 10.1007/s00228-018-2574-6
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in loop diuretic treatment from 2005 to 2014 in Swedish real-life patients with chronic heart failure

Abstract: PurposeLoop diuretics are recommended to treat congestive symptoms in patients with heart failure. However, observational studies have indicated that loop diuretic treatment in heart failure is associated with increased mortality. Therefore, loop diuretic discontinuation or dose reduction, when clinically possible, is recommended. Our aim was to study nationwide temporal trends in loop diuretic treatment from 2005 to 2014 in real-life patients with chronic heart failure.MethodsData from the nationwide Swedish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Several observational studies have reported that high‐dose loop diuretics are associated with poor prognoses in patients with HF 18–21 . A recent Swedish nationwide cohort study reported a trend of decreased prescription rates and dose of loop diuretics for the patients with chronic HF 22 . The SMILE study demonstrated that the baseline dose of oral diuretics decreased from 69.3 to 54.9 mg between 2011 and 2015 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several observational studies have reported that high‐dose loop diuretics are associated with poor prognoses in patients with HF 18–21 . A recent Swedish nationwide cohort study reported a trend of decreased prescription rates and dose of loop diuretics for the patients with chronic HF 22 . The SMILE study demonstrated that the baseline dose of oral diuretics decreased from 69.3 to 54.9 mg between 2011 and 2015 11 .…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] A recent Swedish nationwide cohort study reported a trend of decreased prescription rates and dose of loop diuretics for the patients with chronic HF. 22 The SMILE study demonstrated that the baseline dose of oral diuretics decreased from 69.3 to 54.9 mg between 2011 and 2015. 11 Similarly, in our study, the baseline dose of oral loop diuretics (in furosemide equivalents) gradually decreased between Cohort 1 and Cohort 15.…”
Section: Temporal Trends For Loop Diuresis Treatment In Acute Heart Fmentioning
confidence: 99%
“…Also, it seems patients with higher body mass index receive diuretics more frequently [29]. Interestingly, based on a large scale study, patients with chronic heart failure who depend on the maintenance of their volume balance for a better quality of life used a lower amount of loop diuretics [30]. The information regarding the temporal trends of diuretic utilization among patients which septic shock is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Using prescription data alone has been suggested as a method to identify people with heart failure, although the specificity and sensitivity are lower compared to ICD codes [34]. Another drawback is a potential change in sensitivity/specificity of the proxy between 2007 and 2013, as a result of the decreased use of loop diuretics among people with heart failure over the years [60]. Furthermore, the reasons for drug prescription were not recorded in this study, and the doses of the drugs were not registered.…”
Section: Discussionmentioning
confidence: 99%